Functionality versus gerrymandering and nationalism in administrative geography: lessons from Slovakia. Issue 10 (3rd October 2017) - Halás, Marián; Klapka, Pavel
ABSTRACT: Functionality versus gerrymandering and nationalism in administrative geography: lessons from Slovakia. Regional Studies . A correct definition of administrative regions is one of the crucial factors in the efficient performance of public administration. The paper stresses the advantages of a spatial interaction approach. It builds on four conceptual cornerstones: functional relationships in space, functional regions, the distance–decay function and administrative geography principles. It also includes a presentation of the selected risks that can degrade the correctness of an administrative arrangement. The proposed approach provides administrative regions that follow the principles of spatial efficiency and spatial equity, and the territory of Slovakia is used as an example.